Membrane bioreactors (McGraw-Hill's AccessEngineering., 2013)
"This Water Environment Federation resource presents best practices for the use of membrane bioreactors for wastewater treatment. The book begins with an overview of membrane and biological process fundamentals, followed by coverage of membrane bioreactor system integrated process design. The physical design of features unique to membrane bioreactors and the procurement of membrane equipment are discussed. This authoritative manual also covers the operation of properly designed membrane bioreactor facilities.".